Microstructure and Superelasticity of Cu–Sn Shape-Memory Microwires by Glass-Coated Melt Spinning - Yangyong Zhao; Yuanyuan Bai; Tie Li; Yong Zhang (Metals, 2023)
Cu–Sn shape-memory microw ires were fabricated by a glass-coated melt spinning method. Effects of Sn content on the microstructure and mechanical properties of microwires were investigated. The phase transforms from martensite to austenite with an increase in Sn from 14.0 atomic percent (at.%) to 16.5 at.%. When the Sn content exceeds 16.5 at.%, a highly ordered intermetallic phase, δ, formed. The fracture stress (σf) and the critical stress for martensitic transformation (σMs) increases with an increase in Sn content. The mechanical properties as well as the superelasticity were greatly improved by a high cooling rate in the glass-coated melt spinning method. A bamboo-grained structure was formed in the Cu–Sn microwire with a Sn content of 16 at.% by annealing at 750 °C for 5 h before quenching in water. The results indicate that two opposite strategies of refining the grain size to the micrometer level, or increasing the grain size to a one dimensional size of specimen, e.g., the diameter of the wire, are both effective in improving the superelasticity of the Cu–Sn alloy.